ANALISIS KINERJA KADER POSYANDU MAWAR DI DESA TUNTUNGAN I, KECAMATAN PANCUR BATU, KABUPATEN DELI SERDANG - Suro Rahmadhona Tumanggor; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
Posyandu is a form of Community-Based Health Eflorts (UKBM) which is managed from, by, for and with the community, in order to renew the community and provide convenience to the community in obtaining basic health services. The type of research conducted was qualitative research using interview and observation methods which aimed to obtain in-depth information about the performance of Posyandu Mawar cadres in Tuntungan I Village. It was carried out at the Mawar Posyandu in the work area of the Tuntungan I Village Health Center, Pancur Batu District, Deli Serdang Regency in June 2023 against 3 informants, namely the village head; a Posyandu cadre; and one of the residents who took part in Posyandu activities. The results of this study indicate that the performance of Posyandu Mawar cadres in Tuntungan I Village is in the good and satisfactory category; the service provided by cadres is quite good although there are still some deficiencies; the facilities at Posyandu are sufficient; Posyandu cadres are given training from the Puskesmas although not routinely (once a month) and Posyandu cadres have never received incentives or salaries from the government because they work voluntarily.